"She Came out of mum's Tummy the Wrong way" (Mis) Conceptions Among Siblings of Children with Rare Disorders. Issue 2 (6th September 2014) - Vatne, Torun M.; Helmen, Ingerid Østborg; Bahr, David; Kanavin, Øivind; Nyhus, Livø
Abstract: Misconceptions or uncertainty about the rare disorder of a sibling may cause adjustment problems among children. New knowledge about their misconceptions may enable genetic counselors to provide targeted information and increase siblings' knowledge. This study aims to describe misconceptions and uncertainties of siblings of children with rare disorders. Content analysis was applied to videotapes of 11 support group sessions with 56 children aged 6 to 17. First, children's statements about the disorder (turns) were categorized into the categories "identity, " "cause, " "cure, " "timeline, " and "consequences" and then coded as medically "correct, " "misunderstood, " or "uncertain." Next, turns categorized as "misunderstood" or "uncertain" were analyzed to explore prominent trends. Associations between sibling age, type of disorder, and frequency of misconceptions or uncertainties were analyzed statistically. Approximately 16 % of the children's turns were found to involve misconceptions or uncertainty about the disorder, most commonly about the identity or cause of the disorder. Misconceptions seemed to originate from information available in everyday family life, generalization of lay beliefs, or through difficulties understanding abstract medical concepts. Children expressed uncertainty about the reasons for everyday experiences (e.g. the abnormal behavior they observed). A lack of available information was described as causing uncertainty. Misconceptions and uncertainties were unrelated to child age or type of disorder. The information needs of siblings should always be addressed during genetic counseling, and advice and support offered to parents when needed. Information provided to siblings should be based on an exploration of their daily experiences and thoughts about the rare disorder.